Levels of anxiety and coping with stress in healthcare workers during coronavirus disease 2019 (COVID-19) pandemic - Deniz Deniz Özturan; Asena Keleş Şahin (SERNEV, 2021)
Introduction: The aim of this study is to evaluate anxiety levels and stress coping strategies of healthcare workers during the COVID-19 pandemic.Methods: Data were collected with an online survey using SurveyMonkey application. The research population comprised doctors and other medical staff living in different provinces in Turkey. The online surveys were completed by 354 healthcare workers. Demographic characteristics, severity of clinical anxiety symptoms and coping attitudes of the participants were analyzed. The Beck Anxiety Inventory (BAI) and Stress Coping Strategies Scale were used.Results: The BAI scores of doctors were lower than those of the other healthcare workers (p = 0.037). When compared in terms of depression categories, the two groups were found to be similar (p = 0.060). The levels of coping with stress were similar. The BAI scores of women were significantly higher (p = 0.002). Conclusion: Healthcare workers were observed to mostly develop positive coping attitudes during the COVID-19 pandemic. The results of this study suggest that the stress caused by the outbreak involves excessive load on healthcare workers psychologically.